10-Hydroxy-2-decenoic acid inhibiting the proliferation of fibroblast-like synoviocytes by PI3K–AKT pathway - Wang, Jianguang; Zhang, Wei; Zou, Hai; Lin, Yaoyao; Lin, Ke; Zhou, Zhonghao; Qiang, Jiaping; Lin, Jialiang; Chuka, Chifundo Martha; Ge, Renshan; Zhao, Shujiang; Yang, Xinyu (International immunopharmacology, 2015)
To reveal the mechanism of 10H2DA inhibiting the proliferation of fibroblast-like synoviocytes (FLSs) of RA patients. Cell proliferation, HDAC activity and histone acetylation level of FLS cells treated with 10H2DA were detected by MTT assay, Colorimetric HDAC Activity Assay and Western-blot. Different genes in FLS cells from RA patients were primary cultured and treated with 10H2DA. They were then screened by Human Transcriptome 1.0 ST microarrays and verified by real-time PCR. The results showed dose-dependent and time-dependent decreases in cell viability and HDAC activity in FLSs treated with 10H2DA, and time-dependent induction in the acetylation of H3 and H4 at the same time. 697 different genes were identified by HTA 1.0. The expressions of 7 target genes of the PI3K–AKT pathway were decreased and 4 target genes of cytokine-cytokine receptor interaction were increased verified by real-time PCR. These results imply that 10H2DA is a potential HDACI which inhibits the proliferation of FLS cells by PI3K–AKT pathway. •10H2DA inhibited the activity of HDACs.•697 different genes were screened out between RA and control subjects by HTA1.•The expressions of 7 target genes of the PI3K–AKT pathway were decreased.•4 target genes of cytokine–cytokine receptor interaction were increased.•10H2DA inhibited the proliferation of FLS cells by decreasing PI3K–AKT pathway.